Heart rate and microinflammation in men: a relevant atherothrombotic link. Issue 8 (19th January 2007) - Rogowski, O; Shapira, I; Shirom, A; Melamed, S; Toker, S; Berliner, S
Abstract : Objective and background: To explore the possibility that increased resting heart rate (HR) is associated with a microinflammatory response. Such an association could explain, at least in part, the recently described worse cardiovascular prognosis in individuals with increased HR. Methods: Concentrations of fibrinogen and high-sensitivity C-reactive protein, as well as the absolute number of polymorphonuclear leucocytes, were analysed in a cohort of 4553 apparently healthy men and in those with atherothrombotic risk factors. Results: Following adjustment for age and body mass index, lipid profile and cardiovascular risk factors, a significant (p<0.001) difference was noted between individuals in the first quintile of HR (⩽58 beats/min) and those in the fifth quintile (⩾79 beats/min) regarding all the above-mentioned inflammatory biomarkers, the respective mean values being 7.38 and 8.11 μmol/l, 1.12 and 1.61 mg/l, and 4.23 and 4.74×10 9 /l. Conclusions: Resting HR is associated with a microinflammatory response in apparently healthy men and in those with atherothrombotic risk factors. Sympathetic activation might be a common factor explaining such an association. If confirmed in additional studies, this association might be a relevant target for therapeutic manipulations.